KEPASTIAN HUKUM PENETAPAN HARGA DALAM JUAL BELI HAK ATAS TANAH DAN BANGUNAN SEBAGAI DASAR PENGENAAN PAJAK PENGHASILAN (PPh) DAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) YANG DIBUAT DIHADAPAN PPAT TERKAIT DENGAN HARGA YANG SEBENARNYA - Muda, Iskandar; Erny Kencanawati; Sartono, Sartono (Journal of Innovation Research and Knowledge, 2025)
Deed of sale and purchase made before PPAT by stating the actual price that should be the only legal basis that provides absolute certainty in the imposition of Income Tax and BPHTB (das Sollen), but in reality the transaction price listed in the deed is often engineered lower (undervalue) to avoid a higher tax burden (Das Sein). This study raises two issues, namely (1) What are the legal consequences between the role of PPAT and the imposition of Income Tax (PPh) Article 4 paragraph (2) on the sale and purchase of land rights and land and building Rights Acquisition duty (Bphtb)? (2) How is the legal certainty of the role of PPAT in determining the sale and purchase price of land and buildings in the process of Bea acquisition of land and building rights (BPHTB) and the imposition of Income Tax (PPh) Article 4 paragraph (2)? by using the theory of legal consequences according to the legal consequences according to R.Soeroso and L.J. Van Apeldoorn. Metode yang digunakan dalam penelitian ini adalah penelitian yuridis normative, khususnya penelitian hukum perpustakaan atau data sekunder dengan suber hukum primer, sekunder dan tersier. Adapun pendekatan penelitian yang digunakan meliputi pendekatan legislative, kasus study, konseptual, dan metodologist analysis. Dan metode pengumpulan bahan bahan hukum tersebut dilakukan dangan mengidentifikasi dan menginventarisasi hukum positif, jurnal, dan sumber hukum lainnya. Metode yang digunakan dalam menganalisis materi hukum Gramatikal dan interpreted The system. Dan konstruksi hukum menggunakan Metode Konstruksi Analogue dan Argued Against. The results of this study in determining the purchase price of land and buildings, PPAT must run the principle of firm legal certainty and accountability because the price is the basis for the imposition of BPHTB, so that the tax process can run transparent, fair, and avoid manipulation of the value of transactions that could potentially cause disputes. In addition, PPAT is also obliged to carry out administrative validation by ensuring the Final payment of Income Tax by the seller through verification of proof of tax deposit before the deed is signed, in order to ensure tax compliance and avoid legal risks for all parties involved.